(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article presents a look at some prospects (the need) for the development of ideas about legal means proposed to the scientific community in S. S. Alekseev’s article ‘Legal means: problem statement, concept, classification’. It is pointed out the need for a theoretical and legal understanding of legal and technical regulation as a means of increasing the effectiveness of legal regulation.